PEMBERDAYAAN KOMUNITAS ADAT TERPENCIL DALAM MENINGKATKAN PARTISIPASI SEKOLAH DI DESA HULU SAMPANAHAN - Riadi, Selamat; Nasruddin, Nasruddin; Mattiro, Syahlan; Amin, Faisal; Riduan, M. (Universitas Padjadjaran, 2026)
Remote Indigenous Communities (KAT) in Hulu Sampanahan Village face serious barriers in accessing formal education due to geographic isolation, economic limitations, poor infrastructure, and strong local cultural values. This community service program aimed to increase educational awareness while identifying factors that hinder school participation among KAT in Hulu Sampanahan. The program was carried out through participatory educational outreach and socialization using a Participatory Action Research (PAR) approach, involving village officials, community leaders, and residents. The findings revealed that low school participation is mainly caused by the long distance to secondary schools (33–44 km), severely damaged road conditions, the absence of middle and high schools within the village, and low parental awareness (only about 30% encourage their children to continue to junior high school, and less than 10% aspire for higher education). In addition, more than 70% of children are involved in household and subsistence work. Through the educational sessions attended by 35 households, with 63% actively participating in discussions, the community gained new awareness regarding educational rights, the importance of secondary and higher education, as well as scholarship opportunities accessible to their children. As an impact, the program successfully built initial community awareness of the strategic value of education, while also identifying priority needs such as the establishment of satellite schools, the provision of school transportation, and sustained multi-stakeholder support. Thus, participatory and context-based educational empowerment has proven to be an effective initial step in fostering social transformation in remote Indigenous communities.Komunitas Adat Terpencil (KAT) di Desa Hulu Sampanahan menghadapi hambatan serius dalam mengakses pendidikan formal akibat keterpencilan geografis, keterbatasan ekonomi, buruknya infrastruktur, dan nilai-nilai budaya lokal. Kegiatan pengabdian ini bertujuan untuk meningkatkan kesadaran pendidikan sekaligus mengidentifikasi faktor penghambat partisipasi sekolah pada Komunitas Adat Terpencil (KAT) di Desa Hulu Sampanahan. Kegiatan dilaksanakan melalui edukasi dan sosialisasi berbasis partisipatif dengan pendekatan Participatory Action Research (PAR), melibatkan pemerintah desa, tokoh masyarakat, dan warga. Hasil kegiatan menunjukkan bahwa rendahnya partisipasi sekolah disebabkan oleh jarak ke sekolah menengah yang sangat jauh (33–44 km), kondisi jalan rusak berat, ketiadaan layanan pendidikan menengah di desa, rendahnya kesadaran orang tua (hanya sekitar 30% mendorong anak hingga SMP, dan kurang dari 10% hingga perguruan tinggi), serta keterlibatan lebih dari 70% anak dalam pekerjaan rumah tangga dan aktivitas ekonomi keluarga. Melalui kegiatan edukasi yang diikuti oleh 35 kepala keluarga dengan tingkat partisipasi aktif 63%, masyarakat memperoleh pemahaman baru mengenai hak pendidikan, pentingnya pendidikan menengah dan tinggi, serta peluang beasiswa yang dapat diakses anak-anak mereka. Dampaknya, kegiatan ini berhasil membangun kesadaran awal masyarakat terhadap nilai strategis pendidikan, sekaligus mengidentifikasi kebutuhan prioritas berupa sekolah filial, transportasi pendidikan, dan dukungan multi-stakeholder yang berkelanjutan. Dengan demikian, pemberdayaan pendidikan berbasis partisipasi terbukti menjadi langkah awal yang efektif dalam mendorong transformasi sosial di komunitas adat terpencil.